Bedding behavior in goitered gazelles. Issue 2 (4th March 2021) - Blank, David A.
Abstract : Resting is an essential part of ungulate life that is very important for their comfort and welfare. The bed-site location is crucial for ungulate thermoregulation, concealment, and predation avoidance. The ground's preparation of bed-sites before lying down allows ungulates to recover their energy in fairly comfortable conditions. The bedding behavior is a basic and common pattern in ungulates, but this behavior is still poorly understood. In this paper, I studied the bedding and resting behaviors in goitered gazelles ( Gazella subgutturosa ), which have not yet been investigated until now. I found: (a) goitered gazelles preferred the soft substrate of the dry river beds for their resting places all year round; (b) they searched for comfortable bed-sites with their muzzles lowered and pawed the bed-site with one or both front legs; (c) searching for the best position on the bed-site, they spun around on the bed-site for 90–360º before lying down; (d) scratching bed-sites with the front hooves served rather to increase the softness of the resting place in all seasons than for clearing snow in winter only; (e) the gazelles changed their body side periodically during long lying periods avoiding pressure sores; and (f) to help maintain muscle tone, they stretched their bodies after ending a long resting period. Main functions of bedding behavior and related movements are similar to other ungulate species, but some patterns in goitered gazelles were observed that were unknown resting behaviors of other ungulate species, such as spinning around on the bed-site before lying down and changing body sides during rest.